Customers’ Assessment on the Marketing Mix of Kain Pepper’s Resto Bar at Camarin Road, Caloocan City: Basis for Enhancement of Marketing Strategies: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
These days, customers expect a personalized experience, and conducting customer surveyshas become a trend for seasoned and budding businesses. The establishment is still facingissues. One of those is a lack of marketing advertisements and campaigns, which is a worryfor the restaurant. Despite being fully operational since January 2022, KP struggles to attractnew customers. The lack of a marketing campaign and advertising is the most commonproblem that "KP" faces. Since "KP" only uses its Facebook page to advertise, "KP" missedthe opportunity to offer promotions to all potential customers. This study concluded that bygetting customers' feedback, we suggest that providing more information on the menu mayhelp customers choose what they want to eat and ask what they think needs to be improvedby knowing their purchase decision.Based on the collected data, it can be shown that the assessments of the aforementionedcriteria of the two groups of respondents differ significantly from one another. Itdemonstrates that the null hypothesis is rejected since the t-value (3.38), which is smallerthan the critical value (2.78), is rejected. It concludes that there is a significant differencebetween the customers' assessments of the two groups in terms of price, product, place,and promotion.The findings showed that all of the respondents had favorable opinions on their food, sales,and surroundings. Kain Peppers Resto firmly believes that there is an issue with their price,goods, location, and advertising. The responses from male and female respondents aboutthese criteria, however, varied significantly. KP is aware that there are solutions to deal withthe problem while also advancing their company. The researcher wants to help KP Restodevelop a strong marketing plan. In order to make customers feel comfortable, weresearchers advise firms to make it clear who is permitted entrance and to reinforce to all oftheir clients that discrimination is not accepted. We also recommend that restaurants offerdelectable food at reasonable prices in a pleasant environment. Finally, we recommend thatcompanies use advertising to attract more customers.
Keywords: Business Administration